Hardware-in-the-loop simulation experiments with a hydraulic manipulator model - Ferreira, Jorge A. (2022)
This paper presents the development of a hydraulic SCARA (Selective Complience Assembly Robot Arm) manipulator model to be used in hardware-in-the-loop simulation experiments. Most of the mathematical models are semi-empirical in order to reduce the required simulation time and to perform real time simulations in small cost platforms. The real time simulations run in the xPC platform from Mathworks and commnunicate with the real world through acquisition boards from National instruments. Position control experiments, following typical robot trajectories, were made with PD controllers implemented with operational amplifi ers. The results obtained in the HILS experiments were very satisfactory, considering that semi-empirical models were used.